Structure-based identification of Jervine as a potent dual-targeting inhibitor of cell cycle kinases - Sulaimani, Md Nayab; Imtiyaz, Khadija; Hassan, Md. Imtaiyaz; Husain, Fohad Mabood; Rathi, Aanchal; Farooq, Mir Ovais; Ashraf, Anam; Dohare, Ravins; Sohal, Sukhwinder Singh; Noor, Saba (Frontiers in Pharmacology, 2025)
Mitotic regulators play an essential role in cell cycle progression by ensuring correct chromosomal alignment, segregation, DNA replication, repair, and division, thereby maintaining genomic stability. Aberrant activity of cell cycle kinases, including aurora kinase B (AURKB) and cyclin-dependent kinase 1 (CDK1), might lead to disrupted mitotic checkpoints, causing aneuploidies and uncontrolled proliferation, which are critical hallmarks of cancers. Targeted inhibition of cell cycle kinases is an attractive strategy to combat cancers with minimal side effects. This study employed a comprehensive multi-staged computational approach to discover dual-targeting inhibitors against AURKB and CDK1, which are reported as key promoters of tumorigenesis. High-throughput screening of phytochemicals available in the Indian Medicinal Plants, Phytochemistry, and Therapeutics (IMPPAT) database was conducted to identify common lead/s from top hits. Jervine (IMPHY000366), a steroid alkaloid, emerged as a common compound depicting high binding affinity and ligand efficiency for AURKB and CDK1. In addition, this compound qualified all drug-like filters. After structure analysis, the docked complex was subjected to 300 ns MD simulation studies, confirming structural integrity in AURKB and CDK1 upon binding of Jervine. H-bonding pattern, secondary structural content, free energy landscape, and principal component analysis further supported Jervine’s strong and stable affinity for AURKB and CDK1. Lastly, MMPBSA showed a higher negative free energy in the presence of Jervine than VX-680 when complexed with AURKB. Finally, our results suggest that Jervine is a potent, dual-targeting kinase inhibitor with favourable pharmacokinetic and therapeutic properties, warranting further experimental validation for anticancer drug development.